Intramitochondrial Zn2+ accumulation via the Ca2+ uniporter contributes to acute ischemic neurodegeneration - Yuliya V. Medvedeva; John H. Weiss (Neurobiology of Disease, 2014)
Ca2+ and Zn2+ have both been implicated in the induction of acute ischemic neurodegeneration. We recently examined changes in intracellular Zn2+ and Ca2+ in CA1 pyramidal neurons subjected to oxygen glucose deprivation (OGD), and found that Zn2+ rises precede and contribute to the onset of terminal Ca2+ rises (“Ca2+ deregulation”), which are causatively linked to a lethal loss of membrane integrity. The present study seeks to examine the specific role of intramitochondrial Zn2+ accumulation in ischemic injury, using blockers of the mitochondrial Ca2+ uniporter (MCU), through which both Zn2+ and Ca2+ appear able to enter the mitochondrial matrix. In physiological extracellular Ca2+, treatment with the MCU blocker, Ruthenium Red (RR), accelerated the Ca2+ deregulation, most likely by disrupting mitochondrial Ca2+ buffering and thus accelerating the lethal cytosolic Ca2+ overload. However, when intracellular Ca2+ overload was slowed, either by adding blockers of major Ca2+ entry channels or by lowering the concentration of Ca2+ in the extracellular buffer, Ca2+ deregulation was delayed, and under these conditions either Zn2+ chelation or MCU blockade resulted in similar further delays of the Ca2+ deregulation. In parallel studies using the reactive oxygen species (ROS) indicator, hydroethidine, lowering Ca2+ surprisingly accelerated OGD induced ROS generation, and in these low Ca2+ conditions, either Zn2+ chelation or MCU block slowed the ROS generation. These studies suggest that, during acute ischemia, Zn2+ entry into mitochondria via the MCU induces mitochondrial dysfunction (including ROS generation) that occurs upstream of, and contributes to the terminal Ca2+ deregulation.